Thirty years after the Cairo declaration on population & development: have family planning measurements caught up? - Horanieh, Nour; Witt, Alice; Fall, Marieme; Montt-Maray, Eloisa; Adamjee, Lamiah; Larson, Elizabeth; Gonzalez-Capella, Thais; Cislaghi, Beniamino (Frontiers in Global Women's Health, 2025)
IntroductionThe 1994 International Conference on Population Development (ICPD) initiated the transition of family planning (FP) programmes from focusing on population control to promoting human rights and women's empowerment. The indicators used to measure success of FP programmes, however, continue to focus on estimating modern contraceptive uptake. Contraceptive Prevalence Rate (CPR) and unmet need are the main indicators used. We aim to assess the views of those working within the FP community from the Global North and South on the use of current indicators for FP programmes. While there have been calls for new measures, understanding the barriers to changing existing ones is essential for adopting and implanting these new measures.MethodsWe conducted semi-structured interviews with 31 participants from five distinct groups; academics, NGO workers, government officials, funding agency workers and advocates. Participants were working in countries worldwide, including both the Global North and South; the latter were mostly based in Francophone West Africa. Interviews explored several themes including FP targets and indicators. We applied a thematic analysis.ResultsParticipants' views ranged from those who believed in the need to eradicate current indicators from FP programmes to those expressing contentment with current indicators and their benefit in measuring success. Most of the participants acknowledged the benefit of indicators in assessing progress or as a starting point, yet they identified multiple limitations to their use, including the possibility of implicit coercion, skewing training to focus on long-acting reversible contraceptives (LARCs) promotion, and prioritising modern contraceptive methods over natural ones. Some expressed anxiety that challenging the status quo could lead to funding cuts. Participants identified challenges in adopting new indicators and emphasised that funding for FP programs remains largely concentrated among international agencies based in the Global North, which results in maintaining certain traditional demographic approaches.ConclusionCurrent indicators affect the understanding of success of FP programmes and influence how FP services translate on the ground. We provide international stakeholders' perspectives on the barriers to be overcome to support development of new indicators, including non-use of contraception as a success as long as it is a full, free and informed choice.